Design and simulation of dual-band rectangular microstrip patch array antenna for millimeter-wave - Shahad Dhari Sateaa; Maysam Sameer Hussein; Zainab Ghazi Faisal; Amany Mohammad Abood; Huda Dhari Satea (Institute of Advanced Engineering and Science, 2022)
Microstrip array antennas are essentially for radar and communications systems. They are used to get a needed pattern that cannot be realized with a single element. This paper aims to design and simulate of rectangular microstrip patch array antenna 1 patch (1×1), 2 patches (1×2), and 4 patches (1×4) and improve the performance results. The proposed antenna is simulated by using electromagnetic simulation, computer software technology Microwave studio (CST) printed on Rogers RT5880 (lossy) substrate with dielectric constant 2.2, 0.0009 loss tangent, and thickness 0.1 mm. The simulation results show that the small patch antenna size (1.57 mm × 2 mm) for three designs works at dual bandwidth. The major target of this work is to accomplish an unusual directivity with improved gain for three antenna array designs.